The Relationship Between Psychological Capital and Burnout in Resident Doctors at RSUP. Dr. M. Djamil - nabila, Chika; Rinaldi (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
The purpose of this study was to determine the relationship between psychological capital and burnout in resident doctors at Dr. M. Djamil Hospital. This study used the Psychology capital scale (independent variable) and the MBI-HSS scale to measure Burnout (dependent variable). The sample used was 89 resident doctors SP-1 using a purposive sampling technique. Data analysis in this study used the product moment correlation test with the help of IBM SPSS Statistic 25 for window. The results of this study showed a Pearson Correlatio value of -0.670, which means that there is a negative and significant relationship between psychological capital and burnout in resident doctors at Dr. M. Djamil Hospital. This shows that if the psychological capital of resident doctors increases, there will be a decrease in burnout, and vice versa.